Reproductivity, Productivity and Management System of Indigenous Buffalo (Bubalus bubalis) Cows in Costal Areas of Pirojpur and Borguna District of Bangladesh - Karim, MR; Hossain, MZ; Islam, MR; Parvin, MS; Matin, MA (Progressive Agriculture, 2014)
Twenty five buffalo cows of Mothbaria Upazila of Pirojpur district and another twenty five indigenous buffalo cows of Pathorghata Upazila of Borguna district of Bangladesh were randomly selected and interviewed to collect data on reproductivity (gestation length, birth weight, age of first calving, post partum heat and calving interval), productivity (lactation length and daily milk yield) and management system (general management, housing, feeding, calf rearing and treatment facilities) of indigenous buffalo cows using pre-tested questionnaire during the period from January to June 2010. The reproductive parameters including gestation length, birth weight, age of first calving, post partum heat and calving interval of Mothbaria Upazila of Pirojpur district were 319.56 ± 5.93 days, 24.28 ± 4 kilograms, 50.88 ± 1.71 months, 153.6 ± 6.13 days, 547.92 ± 10.88 days respectively whereas in case of Pathorghata Upazila of Borguna district these parameters were 319.12 ± 4.69 days, 24.12 ± 3.6 kilograms, 51 ± 1.8 months, 153.44 ± 6.78 days, 547.24 ± 14.32 days respectively. The productive parameters including lactation length and daily milk yield of Mothbaria Upazila of Pirojpur district were 286.12 ± 11.27 days and 3.33 ± 0.68 liters/day respectively while in case of Pathorghata Upazila of Borguna district these parameters 290.44 ± 10.92 days and 3.43 ± 0.744 liters/day respectively. So, reproduction and production are almost regular comparing with other published reports with the exception of age of first calving which is almost 12 months later than the buffaloes of other countries. It could be concluded that the buffalo owners of these areas do not follow any scientific method of buffalo husbandry; they just follow traditional rearing system. The farmers mostly use buffaloes for draught purpose in these costal areas. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19113 Progress. Agric. 24(1&2): 117 - 122, 2013